Befriending Services for Culturally Diverse Older People. Issue 7 (3rd October 2019) - Wiles, Janine; Morgan, Tessa; Moeke-Maxwell, Tess; Black, Stella; Park, Hong-Jae; Dewes, Ofa; Williams, Lisa Ann; Gott, Merryn
ABSTRACT: Befriending services may address loneliness and social isolation amongst older people. However social diversity is rarely reported in investigations of befriending services. The views of non-users are also rarely explored. In this research, we explored older adults' experiences of, and attitudes towards, a befriending service, among service users and non-service users, drawing on interviews and focus groups with 76 older adults, 10 volunteer visitors, and 20 service providers. Participants agreed that the befriending service helped alleviate social isolation and loneliness and that supportive services to foster connection are needed. Barriers to engagement included lack of knowledge, appropriateness of services and feeling undeserving. The befriending service was most successful when a match went beyond a transactional 'professional-client' relationship to resemble genuine friendship, underpinned by mutual interests and norms of reciprocity and reliability. We also identified five clear ideas about what characterizes an ideal supportive service; supported opportunities for getting out, genuine and reciprocal relationships, reliability, visitor characteristics, and connecting people to their culture. Befriending adds to social networks, and enhances connectedness to the community. Loneliness is alleviated when mutually beneficial and genuinely reciprocal relationships develop. However, group interventions or connections to community groups may be more appropriate for some.